2021
DOI: 10.3390/pathogens10060645
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Avian Haemosporidian Parasites in Southern Iran

Abstract: Avian haemosporidians are widespread and diverse and are classified in the genera Plasmodium, Haemoproteus, Leucocytozoon, and Fallisia. These species are known to cause haemosporidiosis and decreased fitness of their hosts. Despite the high diversity of habitats and animal species in Iran, only few studies have addressed avian haemosporidians in this geographic area. This study was performed in the south and southeast of Iran during the bird breeding seasons in 2017 and 2018, with the aim to partly fill in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
2
8
1
Order By: Relevance
“…For example, in Bulgaria, songbirds exhibited an infection rate of 58.04% [8], while in Austria, the rate was 43.7% [9]. Similar studies conducted in Iran reported a prevalence of haemosporidian infections of 35.75% in northern regions [10] and 51.1% 2 in southern parts of Iran [11]. The prevalence and transmission of blood parasites depend on factors such as vector presence and bird population density [12].…”
Section: Introductionmentioning
confidence: 80%
“…For example, in Bulgaria, songbirds exhibited an infection rate of 58.04% [8], while in Austria, the rate was 43.7% [9]. Similar studies conducted in Iran reported a prevalence of haemosporidian infections of 35.75% in northern regions [10] and 51.1% 2 in southern parts of Iran [11]. The prevalence and transmission of blood parasites depend on factors such as vector presence and bird population density [12].…”
Section: Introductionmentioning
confidence: 80%
“…Oak ( Quercus ) forest, covering most of Zagros, provides a good habitat for wild birds. Climatically, the western region is warmer than the eastern region, with hot summers and moderate winters, and has better conditions for the propagation of arthropod vectors (Ghaemitalab et al 2021).…”
mentioning
confidence: 99%
“…3). PADOM05 was the most frequent lineage isolated from House Sparrows in Iran (Nourani et al 2018; Ghaemitalab et al 2021). Some Haemoproteus spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations